Interregional and international knowledge flows in medium technology sectors - The role of formal and informal institutions - Silviya Draganinska; Ruediger Wink (European Regional Science Association (ERSA), 2005)
Many scientific papers deal with the relevance of geographical proximity for the generation, acquisition and exploitation of new knowledge. SME in medium technology sectors serve as typical examples for firms, which are dependent on geographical proximity to sales markets and knowledge, as they have only limited resources for international knowledge strategies and need only incremental improvements integrated within tacit routine-based knowledge due to the maturity of their technologies. Increasing internationalisation of production systems, how-ever, challenges geographically concentrated firms, and many policy initiatives and regional agencies have been introduced to help SME to extend their scope of knowledge flows. The paper will present a theoretical model on institutional prerequisites for SME to overcome the need for geographical proximity in the context of innovation and learning. The model is based on innovation system and knowledge management approaches but extend these approaches to evolutionary institutional processes including the role of cognitive patterns and trust. First empirical results of investigating a cluster in the German machinery sector will be used to proof the suitability of the theoretical model and to discuss policy recommendations on the national and supranational level.
Keywords: 330